2001
DOI: 10.1051/0004-6361:20011323
|View full text |Cite
|
Sign up to set email alerts
|

Short-term emission line and continuum variations in Mrk 110

Abstract: Abstract. We present results of a variability campaign of Mrk 110 performed with the 9.2-m Hobby-Eberly Telescope (HET) at McDonald Observatory. The high S/N spectra cover most of the optical range. They were taken from 1999 November through 2000 May. The average interval between the observations was 7.3 days and the median interval was only 3.0 days. Mrk 110 is a narrow-line Seyfert 1 galaxy. During our campaign the continuum flux was in a historically low stage. Considering the delays of the emission lines w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 23 publications
5
81
0
2
Order By: Relevance
“…Spectral observations on a daily basis are needed to solve this question that the He ii λ4686 line originates in the innermost region while the Hα line originates in more exterior regions than Hβ as has been found e.g. in Mrk 110 (Kollatschny et al 2001) We compare our observed velocity-delay pattern with model calculations of Welsh & Horne (1991), Perez et al (1992), O'Brien et al (1994), Horne et al (2004), and with results of Mrk 110 (Kollatschny 2003).…”
Section: D Velocity Mapmentioning
confidence: 76%
See 3 more Smart Citations
“…Spectral observations on a daily basis are needed to solve this question that the He ii λ4686 line originates in the innermost region while the Hα line originates in more exterior regions than Hβ as has been found e.g. in Mrk 110 (Kollatschny et al 2001) We compare our observed velocity-delay pattern with model calculations of Welsh & Horne (1991), Perez et al (1992), O'Brien et al (1994), Horne et al (2004), and with results of Mrk 110 (Kollatschny 2003).…”
Section: D Velocity Mapmentioning
confidence: 76%
“…It is known from other galaxies (e.g. Mrk 110, Kollatschny et al 2001) that the He ii λ4686 line exhibits shorter delays with respect to the ionizing continuum than the Hβ line. The apparent negative delay of two light-days with respect to the continuum light curve at 5180 Å might be caused by a general systematic error or by an alternative possibility that the continuum flux at 5180 Å does not correspond to the ionizing continuum flux.…”
Section: -D Ccf Of the Hα And Hβ Line Profilesmentioning
confidence: 95%
See 2 more Smart Citations
“…In his sample of ∼ 20 AGN he found firm evidence that both the [Fe VII] λ6087 and [Fe X] λ6375 emission lines varied (during a period of a few years) for only one source, namely, NGC 5548, which is the subject of this paper, and tentative evidence for another seven sources (including NGC 4151). Then, within a general optical variability campaign on the source Mrk 110 lasting for half a year, Kollatschny et al (2001) reported strong [Fe X] variations. More recently, follow-up optical spectroscopy of a handful of objects with unusually prominent coronal lines selected from the SDSS showed that in half of them the coronal lines strongly faded (by factors of ∼ 2 − 10), making these sources candidates for stellar tidal disruption events (Komossa et al 2009;Yang et al 2013).…”
Section: Introductionmentioning
confidence: 99%